2010
DOI: 10.1080/10790268.2010.11689719
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Alpha-Lipoic Acid in Experimental Spinal Cord Injury in Rats

Abstract: Background: Oxidative stress is a mediator of secondary injury to the spinal cord following trauma. Objective: To investigate the putative neuroprotective effect of ex-lipoic acid (LA), a powerful antioxidant, in a rat model of spinal cord injury (SCI). Methods: Wistar albino rats were divided as control, vehicle-treated SCI, and LA-treated SCI groups. To induce SCI, a standard weight-drop method that induced a moderately severe injury (1 00 g/cm force) at T1 0 was used. Injured animals were given either 50 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 41 publications
4
34
0
Order By: Relevance
“…In the same injury model, severe axonal membrane damage was observed, but was not apparent until several days post-injury [49]. Toklu et al found myelin degradation at 7 days post-injury correlated with lipid peroxidation and DNA fragmentation [116]. These data are consistent with the hypothesis that diffusive elevation of acrolein precedes and leads to membrane disruption and subsequent cell death following in vivo spinal cord trauma.…”
Section: Concentration Duration Of Exposure and Compounding Factsupporting
confidence: 54%
“…In the same injury model, severe axonal membrane damage was observed, but was not apparent until several days post-injury [49]. Toklu et al found myelin degradation at 7 days post-injury correlated with lipid peroxidation and DNA fragmentation [116]. These data are consistent with the hypothesis that diffusive elevation of acrolein precedes and leads to membrane disruption and subsequent cell death following in vivo spinal cord trauma.…”
Section: Concentration Duration Of Exposure and Compounding Factsupporting
confidence: 54%
“…These include methylene blue, mexilitine, thiopental, β-glucan, cyclosporine A, erythropoietin and α-lipoic acid. 34 Although some of these are probably true chemical antioxidants (for example, methylene blue, edaravone, α-lipoic acid), others may work indirectly by induction of endogenous antioxidant defenses (for example, N-acetylcysteine), reduction of mitochondrial dysfunction and its associated free-radical leakage (for example, cyclosporine A) or by enhancement of cell membrane repair mechanisms (for example, polyethylene glycol). All these data support the idea that antioxidant therapy may be beneficial in SCI patients.…”
Section: Antioxidants In Sci Treatmentmentioning
confidence: 99%
“…These include methylene blue [110], mexilitine [111], thiopental [112], β-glucan [113], N-acetylcysteine [114], γ-glutamylcysteine [18], polyethylene glycol [115], edaravone (MCI186), cyclosporine A [116], NIM811 [117,118], erythropoietin [119] and α-lipoic acid [120]. Although some of these are probably true chemical antioxidants (e.g., methylene blue, edaravone, α-lipoic acid), others may work indirectly by induction of endogenous antioxidant defenses (e.g., N-acetylcysteine, γ-glutamylcysteine), reduction of mitochondrial dysfunction, and its associated free radical leakage (e.g., cyclosporine A, NIM811) or by enhancement of cell membrane repair mechanisms (e.g., polyethylene glycol).…”
Section: Efficacy Of Miscellaneous Antioxidants In Sci Modelsmentioning
confidence: 99%